2020
DOI: 10.4155/bio-2020-0188
|View full text |Cite
|
Sign up to set email alerts
|

China Nmpa Perspective on Clinical Evaluation of Sars-Cov-2 Antibody Test Reagents in the Process of Emergency Approval

Abstract: Coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The SARS-CoV-2 antibody testing an important supplement to nucleic acid testing. In the process of emergency approval, the Center for Medical Device Evaluation of the China National Medical Products Administration released The Key Points of Technical Review for the Registration of SARS-CoV-2 Antigen/Antibody Detection Reagents. The Clinical Study Requirement section of the Key Point has put forw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In periods of high viral load, Zhan et Several researchers concentrated on the potential applications of ADRs. Lv et al reviewed the methodologies and requirements for assessing the clinical performance of quick diagnostic tests for SARS-CoV-2 antigen detection and intended application scenarios of ADRs (30). Hauser et al found that the LIAISON SARS-CoV-2 antigen test had excellent specificity but low sensitivity and should only be used for preliminary screening (31).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In periods of high viral load, Zhan et Several researchers concentrated on the potential applications of ADRs. Lv et al reviewed the methodologies and requirements for assessing the clinical performance of quick diagnostic tests for SARS-CoV-2 antigen detection and intended application scenarios of ADRs (30). Hauser et al found that the LIAISON SARS-CoV-2 antigen test had excellent specificity but low sensitivity and should only be used for preliminary screening (31).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Center for Medical Device Evaluation of the National Medical Products Administration (NMPA) issued ‘Key Points of Technical Review for Registration of SARS-CoV-2 Antigen/Antibody Detection Reagents’ [ 10 ], which, as a guidance of registration, provides a detailed description of the premarket evaluation methods and indicators for evaluation for such products [ 11 ]. Previously, the authors published an article that analyzed the requirement for antibody detection reagents [ 12 ]. Based on the Key Points document and the authors’ review practice, this article focuses on the clinical research of antigen detection reagents to explain the evaluation methods and requirements of clinical performance of SARS-CoV-2 antigen detection reagents, then analyzes the application scenarios and intended use of antigen detection reagents in the diagnosis of SARS-CoV-2 infections.…”
mentioning
confidence: 99%